Alginate as an Efficacious Treatment for GERD Patients: A Literature Review - Ninda Septia Yuspar; Suyata (Scientific Journal, 2025)
Gastroesophageal reflux disease (GERD) is a medical condition defined by the retrograde flow of gastric contents into the esophagus, leading to various symptoms.  The principal therapy for GERD consists of proton pump inhibitors (PPIs).  Nevertheless, PPIs demonstrate reduced effectiveness in patients with non-erosive GERD or unusual symptoms.  Alginates operate by forming a gel "raft" that floats on the gastric contents, serving as a physical barrier against reflux.  Multiple studies demonstrate that alginate is more effective than antacids in alleviating GERD symptoms and has a longer duration of action.